Anticipating the experience of being old - Duarte, Suzana Filomena Cardoso (2015)
The project "Anticipating the Experience of Being Old", aims to provide an experience of being old through the use of a simulator. The equipment allows to simulate the changes that occur in the human body as it ages: posture, dexterity, balance, touch, vision and hearing. It's possibleto provide an opportunity to experience the limitations, and understand what old people feels